Visualisasi Wanita Indonesia dalam Majalah Pria Dewasa - Diani Apsari; Didit Widiatmoko Soewardikoen (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2010)
Women usually visualized as model for ads or illustration with the purpose of gaze. Mostly representation of women in mass media related with tradition and culture. Fashion manner and attitude of Indonesian women is one of eastern tradition in Indonesian culture. Today male magazines are Indonesian publication, showing Indonesian woman as their models. How is the visualization pattern built the image of Indonesian Woman? Through visual interpretation and content analysis from sampling of male magazines(For Him Magazine or FHM and Male Emporium or ME), we could find that the image of Indonesian women as eastern tradition shifted and faded toward emphasizing high sex appeal that exploits certain parts of their bodies. Indonesian women has represented almost the same manner as western women on male magazines.